Ethical and Social Challenges in Research with Children Exposed to Forced labour, Exploitation, and Trafficking - Agyare, Patrick (Technium Social Sciences Journal, 2021)
This article explores the ethical and social challenges in research with children exposed to forced labour, exploitation, and trafficking. It examines whether the participation of children in evidence generation has the potential to affect them and how the researcher avoids potential discomfort. This requires investigating the multiple issues and contexts that affect the children. Essentially, conducting a child-centred evidence generation is ethically reasonable based on how such investigation is carried out and on how a child is affected by the research activities. The process of recruiting participants, avoiding potential harm, ensuring privacy, anonymity and confidentiality corresponds to the best possible regulation, in full respect of the interests of children. What is pursued is a child-centred evidence generation, capable of responding in an acceptable way, from an ethical point of view to the question about the methodology of the research itself. In addition, child-centred research enhances the sharing of perspectives and insights, which break down the barriers of exclusion. Against this background, this article contributes to the identification, interpretation, and clarification of ethical and social questions that arise in relation to child-centred evidence generation. Similarly, it furthers awareness on the significance of ethical reflection and in making informed decisions and choices to mitigate against potential harm to participants during and after the research.